Types Verbal Reduplication In Toba Batak: A Study On Psalmen In The Bibel - Ruth Friska Silitonga; Esron Ambarita; Vivi Novalia Sitinjak (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The objective of this research are find out the types of verbal reduplication in Toba Batak:a study on Psalmen in the Bibel .This research was carried out by using descriptive qualitative method. The data are taken from Psalmen in the Bibel. The result of this research are three types of verbal reduplication namely in the full reduplication found 5 verbal reduplication in Toba Batak, partial reduplication found as 10 verbal reduplication in Toba Batak, affixed reduplication found 5 verbal reduplication in Toba Batak.